Computer-generated pornography and convergence: Animation and algorithms as new digital desire. (April 2019) - Saunders, Rebecca
This article is one of the first to consider the digital phenomenon of computer-generated imagery (CGI) pornography, a highly significant site of convergence that combines the technologies, cultures and aesthetics of digital animation, video games and pornographic film. As much of this controversial new content is produced through the hacking of licensed video game franchises, CGI pornography typifies the democratic possibilities of the digital economy. However, this bizarre digital subculture exemplifies too the tension between ludic and labour-intensive digital practises: its production is embedded simultaneously in the anti-productive play of gaming, hacking and pornography, and in the intensive, neo-liberal labour practises associated with free labour and the video game industry. This article explores CGI porn as a specific site of convergence that fundamentally alters the aesthetics and function of digital pornography and relatedly the libidinal subject that is interpolated in this crucial aspect of digital culture. The filmic genre of pornography has a long tradition of producing affective engagement through vicarious access to the material body; its evocations of veracious materiality and presence are only amplified in a digital culture of virtuality and dematerialization. This article analyses how the technological construction of CGI porn is foregrounded in its images and films, highlighting the codes and patterns of the genre and blending them with a stark revelation of the restrictions and capabilities of CGI technology. The article explores how multiple instances of hypermediacy and hypersignification in CGI porn expose and affectively engage with the fact of convergence itself: that is, revealing technological capacities and limitations of digital animation and eroticizing its interpenetration with the films' diegeses, aesthetics and representations of movement become the central function of this new cultural output. The libidinal focus of this type of digital pornography fundamentally shifts, then, away from the human body and the attempt to gain vicarious imagistic access to it through digital technologies. Instead, the labour of the animator, and the coding and characters they borrow from video game designs, become the libidinal focus of computer-generated pornography. As this new digital phenomenon uncovers and eroticizes the workings of CGI, so it dismantles the veracity and materiality promised by 'real body' digital pornography: CGI porn's stark foregrounding of its technological constructedness clarifies the artificiality of its 'real body' counterpart. This article posits, then, an important new site of convergence. Pornography is a central node in the culture, politics and economics of digital technology, and the ways in which its convergence with CGI practises and video game culture has produced not just an entirely new digital phenomenon, but has fundamentally altered digital pornography's conception of the desirous subject and the material body, are crucial.